GC-Fusion frames - Faroughi, M. H.; Rahimi, A.; Ahmadi, R. (Methods of Functional Analysis and Topology, 2010)
In this paper we introduce the generalized continuous version of fusion frame, namely gc-fusion frame. Also we get some new results about Bessel mappings and perturbation in this case.